Novel markers of cell kinetics to evaluate progression from cirrhosis to hepatocellular carcinoma. - Quaglia, A; McStay, M; Stoeber, K; Loddo, M; Caplin, M; Fanshawe, T; Williams, G; Dhillon, A (2006)
BACKGROUND: We investigated cell cycle kinetics of nodular lesions in cirrhosis to differentiate hepatocellular carcinoma (HCC) from its precursor lesions. METHODS: Twelve small HCC, 10 regenerative (RN), six large regenerative (LRN), and five dysplastic nodules (DN), identified in explant cirrhotic livers of five consecutive patients transplanted at Royal Free Hospital in 2002. Immunoperoxidase for MCM2, geminin and Ki67 was performed and the percentage of positive cells counted. RESULTS: The proportion of cells expressing MCM2 was more than those expressing Ki67, which in turn was more than those expressing geminin (overall median=16%, 2% and 0.5%, respectively, P<0.001). There was a statistically significant trend of increasing Ki67 expression (P=0.006), from RN to HCC; this trend was not statistically significant for geminin (P=0.18) or MCM2 (P=0.51). The median percentage of cells expressing Ki67 was 1% in RN, 0.5% in LRN, 2.2% in DN and 5.4% in HCC. The combination of these markers identified four different cell kinetics patterns: 'resting' (G0 cells: MCM2 -ve, Ki67 -ve, geminin -ve); 'licensed' (MCM2 +ve, Ki67 -ve, geminin -ve); 'slowly growing' (G1 phase arrest, MCM2 +ve, Ki67 +ve, low (0.4%) geminin) and expanding (MCM2 +ve, Ki67 +ve, geminin +ve) nodules. CONCLUSIONS: The combination of MCM2, geminin and Ki67 could represent a valuable tool in the understanding of HCC progression in cirrhosis.